End of life experiences of patients with advanced cancer in Myanmar: Results from the APPROACH study. Issue 6 (23rd June 2020) - Mon, Ssu Wynn; Ozdemir, Semra; Zu, Wah Wah Myint; Win, Han; Maw, Myo Myint; Win, Khin Cho; Thant, Kyaw Zin; Teo, Irene; Krishnan, Anirudh; Goh, Cynthia Ruth; Finkelstein, Eric A.; Malhotra, Chetna
Abstract: Background: Access to palliative care services is essential for attaining universal health coverage for patients with a terminal cancer. Despite this, many patients with advanced cancer in low‐income countries, such as Myanmar, suffer at the end of life (EOL) due to little or no access to palliative care. However, actual evidence on EOL experiences of cancer patients in Myanmar is lacking. This paper aims to describe various dimensions of EOL experiences among patients with an advanced cancer from the largest public hospital in Myanmar. Methods: We surveyed 195 patients with stage IV cancer seeking care from outpatient oncology clinics to assess their quality of life, pain severity, pain medications taken, quality of communication with doctors, nursing care and health care coordination, and desire to end life sooner. We assessed socioeconomic status (SES) differences in each patient outcome using separate multivariate linear/logistic regressions. Results: Forty‐one percent of the patients in our sample reported that they wish their life would end sooner. Low SES cancer patients had significantly worse quality of life, reported poor health care coordination and were more likely to report severe pain compared to high SES cancer patients visiting the same hospital. Conclusion: To improve quality of life and pain management and to reduce EOL distress among patients with advanced cancer, there is a pressing need to develop and invest in hospital and community‐level palliative care services in Myanmar.